Biesiespoort revisited: a case study on the relationship between tetrapod assemblage zones and Beaufort lithostratigraphy south of Victoria West - Day, Michael O.; Rubidge, Bruce S. (Evolutionary Studies Institute, 2018)
The relationship between the tetrapod assemblage zones of the South African Karoo Basin and the lithostratigraphic divisions of the Beaufort Group is well-established, and provides an independent means of dating fossil occurrences. However, this relationship may not be consistent across the basin; a discrepancy exists between the historical tetrapod assemblages in the vicinity of Victoria West, Northern Cape Province, and the expected tetrapod assemblage zones based on mapped geology. In order to examine this disconnect, we collected fossils at two localities close to Biesiespoort railway station, a locality that was visited on a number of occasions by Robert Broom. Our fossil samples support the biostratigraphic determinations of Broom and thus confirmthat the stratigraphic extent of the biozones at these localities differs from their type areas further south. The reasons for this are unclear but could be related to the northward younging of the lithological units, implying complex depositional processes, or result from difficulties in mapping. Nevertheless, caution should be exercised when using mapped geology near Victoria West as a guide to the age of fossils found there.
Keywords: Tropidostoma; Cistecephalus; biostratigraphy; Karoo; Beaufort Group; Victoria West